Progress in the Chemistry of Organic Natural Products 110 Cheminformatics in Natural Product Research - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi.; Asakawa, Yoshinori; Liu, Ji-Kai.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book summarizes important aspects of cheminformatics that are relevant for natural product research. It highlights cheminformatics tools that help to match natural products with their respective biological targets or off-targets, and discusses the potential and limitations of this approach.
Resources for chemical, biological, and structural data on natural product -- The pharmacophore concept and its applications in computer-aided drug design -- Chemical space of natural products -- Cheminformatics analysis for natural product fragments -- A toolbox for the identification of modes of action of natural products -- A SWOT analysis of Cheminformatics in natural product research -- Open access prediction tools for natural products. Case study: hERG blockers.
Keywords: Chemistry, Organic; Pharmaceutical chemistry; Medicinal chemistry; Organic Chemistry; Pharmaceutics; Medicinal Chemistry